Economic evaluations of technologies used in health organizations: Integrative review (Research, Society and Development, 2025)
Objective: To map the main economic evaluations of technology used in health organizations. Method: This is an integrative review, with 6 stages (Souza et al, 2010) with research in the databases, with articles published between 2018 and November 19, 2022. Studies with health economic evaluations (HEE) with economic indicators of results and costs of interventions from the perspective of health organizations. Studies with no economic data, without comparative economic analyses, literature reviews, articles with unavailable texts, opinions and decisions of government bodies were excluded. Results: At the end of the selection, 13 studies were considered in this review, a small amount of HEE and an incidence in economically developed countries can be seen. Discussion: The articles present relevant data, however it is necessary to evolve with the use of the concepts of the criteria of the types of HEE, an effective methodology needs to observe the perspective of the study, its time horizon and the costs and results related to the decision makers from that perspective. Final considerations: It is essential to include in the next HEE indicators valued with human resources, indirect costs, length of stay and better mapping and detailing of costs from the perspective of health organizations.